Debaixo da lona: reportagem transmídia e perfis audiovisuais sobre a história de artistas circenses - Mussato, Ariádne [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Circus and circus art have been practiced all over the world since Antiquity and have undergone several modifications until they reach the stage format known to us today. In Brazil, the circus came with influences from other countries and gradually became one of the most popular popular entertainment with genuinely Brazilian characteristics. This work has the purpose of tracing the main landmarks of the circus in Brazil and, also, telling the life story of artists who survive from the circus culture from a journalistic bias. The methodology used was the exploratory research, through analysis of documents and books, verification of contents and sources and oral interviews to collect testimonials. The result is a transmedia report and six audiovisual profiles that tell the life trajectory of circus artists and, consequently, the circus in Brazil.

O circo e a arte circense são praticados no mundo desde a Antiguidade e passaram por diversas modificações até chegarem ao formato de picadeiro que conhecemos hoje. No Brasil, o circo chegou com influências de outros países e, aos poucos, tornou-se um dos mais conhecidos entretenimento popular com características genuinamente brasileiras. Este trabalho tem por finalidade traçar os principais marcos do circo no Brasil e, também, contar a história de vida de artistas que sobrevivem da cultura circense, a partir de um viés jornalístico. A metodologia utilizada foi a pesquisa exploratória, por meio de análises de documentos e livros, apuração de conteúdo e fontes e entrevistas orais para colher depoimentos. O resultado é uma reportagem transmídia e seis perfis audiovisuais que contam a trajetória de vida de artistas circenses e, consequentemente, do circo no Brasil.
Keywords: Jornalismo; Circos - Brasil; Entretenimento; Artistas circenses